The Iconic Philippine Coral Reef at Steinhart Aquarium: The Husbandry, Welfare, Behavior, and Veterinary Care Considerations of a Large Multi-Taxa Living Coral Reef System - Lana Krol; Brenda Melton; J. Charles Delbeek; Freeland H. Dunker; Bart Shepherd (Journal of Zoological and Botanical Gardens, 2023)
In 2008, Steinhart Aquarium at the California Academy of Sciences in San Francisco, CA, USA, unveiled a brand new facility with the 212,000 gallon Philippine Coral Reef habitat as its iconic centerpiece. Designing and managing a system that consists of a living reef this large, with associated invertebrates and teleosts, has been a challenge for the aquarium’s husbandry and veterinary teams. Establishing appropriate lighting, water quality, and flow has required a scientific approach and resulting adjustments to the original habitat design. The medical management of reef species has required an in-habitat approach as well as trial-and-error therapeutics. Determining the criteria for assessing the welfare of corals and other tank inhabitants has been a shifting process that has heavily utilized photography-tracked changes and other quantitative parameters as baselines. This report details the successes and limitations of establishing the environmental and veterinary management of this mesocosm. The consideration of interplay between species is discussed, and recommendations for monitoring welfare both on an individual and tank level are made. Making adjustments for the benefit of the exhibit and its animals is key for the unique aquarium displays that comprise captive coral reef systems.